Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Simulation of recurring defoliation by multiple insects shows lasting consequences for carbon storage in temperate oak forests - Jane R. Foster; Robert M. Scheller; Brian R. Sturtevant; Philip A. Townsend; Brian Miranda; David J. Mladenoff (Forest Ecology and Management, 2026)

Integrating nitrogen and carbon cycling into LANDIS-II/PnET-Succession to improve forest landscape modeling: methods and sensitivity analyses - Zaixing Zhou; Eric J. Gustafson; Scott V. Ollinger; Andrew P. Ouimette; Brian R. Miranda; Matthew J. Duveneck; Jane R. Foster; Brian R. Sturtevant; Dustin R. Bronson; Danelle Laflower (Ecological Modelling, 2025)

Discovery of novel biopesticides from an agricultural disease nursery – a proof of concept study - Leah Gauthier; Adam Foster; Christopher W. Kirby; Brian Wagner (Phytochemistry Letters, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The Coastal Ocean Environment Summer School In Nigeria and Ghana: The Value of Long-Term, Sustained Capacity Sharing - Brian Arbic; Johnson Adjetey; Andrews Agyekumhene; Mosunmola Akinwunmi; Lailah Akita; Lois Anderson; Joseph Ansong; Kwasi Appeaning Addo; Eunice Asamoah; Olawale Awe; Christian Buckingham; Janae’ Collier; et al. (Oceanography, 2025)
The Coastal Ocean Environment Summer School In Nigeria and Ghana (COESSING; https://coessing.org) has been run for one week every year since 2015. The school, an endorsed project of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030), has provided a platform for approximately 1,000 scientists from Africa, the United States, and Europe to exchange scientific knowledge, to network, to learn, and to collaborate. Our interdisciplinary, multicultural, and multi-institutional approach offers a model for knowledge exchange across the globe and across different educational levels.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Radiosensitivity and Biological Effects of Gamma and X-Rays on Germination and Seedling Vigour of Three Coffea arabica Varieties - Keji Emmanuel Dada; David Adedayo Animasaun; Oba Toyin Mustapha; Souleymane Bado; Brian P. Foster (Journal of Plant Growth Regulation, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

Comparative performance evaluation of handpump water-supply technologies in northern Kenya and The Gambia - Tim Foster; Brian McSorley; Juliet Willetts (Hydrogeology Journal, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

Utility of spherical human liver microtissues for prediction of clinical drug-induced liver injury - William R. Proctor; Alison J. Foster; Jennifer Vogt; Claire Summers; Brian Middleton; Mark A. Pilling; Daniel Shienson; Monika Kijanska; Simon Ströbel; Jens M. Kelm; Paul Morgan; Simon Messner; et al. (Archives of Toxicology, 2017)

Historic grazing in southern New England, USA, recorded by fungal spores in lake sediments - Maria E. Orbay-Cerrato; W. Wyatt Oswald; Elaine D. Doughty; David R. Foster; Brian R. Hall (Vegetation History and Archaeobotany, 2017)

Nanoparticles coated with the tumor-penetrating peptide iRGD reduce experimental breast cancer metastasis in the brain - Amanda M. Hamilton; Sallouha Aidoudi-Ahmed; Shweta Sharma; Venkata R. Kotamraju; Paula J. Foster; Kazuki N. Sugahara; Erkki Ruoslahti; Brian K. Rutt (Journal of Molecular Medicine, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Oral Cancer Chemotherapy Adherence and Adherence Assessment Tools: a Report from North Central Cancer Group Trial N0747 and a Systematic Review of the Literature - Krishna Patel; Nathan R. Foster; Ann Farrell; Nguyet Anh Le-Lindqwister; Josy Mathew; Brian Costello; John Reynolds; Jeffrey P. Meyers; Aminah Jatoi (Journal of Cancer Education, 2013)

Prediction of Human Metabolic Clearance from In Vitro Systems: Retrospective Analysis and Prospective View - David Hallifax; Joanne A. Foster; J. Brian Houston (Pharmaceutical Research, 2010)

Plasmids captured in C. metallidurans CH34: defining the PromA family of broad-host-range plasmids - Géraldine A. Van der Auwera; Jaroslaw E. Król; Haruo Suzuki; Brian Foster; Rob Van Houdt; Celeste J. Brown; Max Mergeay; Eva M. Top (Antonie van Leeuwenhoek, 2009)

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Milk thistle and indinavir: a randomized controlled pharmacokinetics study and meta-analysis - Edward Mills; Kumanan Wilson; Mike Clarke; Brian Foster; Scott Walker; Beth Rachlis; Nick DeGroot; Victor M. Montori; Wayne Gold; Elizabeth Phillips; Stephen Myers; Keith Gallicano (European Journal of Clinical Pharmacology, 2005)

Activity of elements from the tobacco cryptic promoter, tCUP, in conifer tissues - Lining Tian; Keqiang Wu; Caroline Levasseur; Thérèse Ouellet; Elizabeth Foster; Marysia Latoszek-Green; Susan Sibbald; Brian Miki; Armand Seguin; Daniel C. W. Brown (In Vitro Cellular & Developmental Biology - Plant, 2003)

Vegetation variation across Cape Cod, Massachusetts: environmental and historical determinants - Glenn Motzkin; Robert Eberhardt; Brian Hall; David R. Foster; Jonathan Harrod; Dana MacDonald (Journal of Biogeography, 2002)
Aim We evaluate environmental and historical determinants of modern species composition for upland vegetation types across Cape Cod, Massachusetts, a region that supports numerous uncommon species assemblages that are conservation priorities. Location The study area encompasses the entire peninsula of Cape Cod, Massachusetts, USA. Methods Historical changes in land‐use and land‐cover across the study region were determined from historical maps and documentary sources. Modern vegetation and soils were sampled and land‐use and fire history determined for 352 stratified‐random study plots. Ordination and classification were used to assess vegetation variation, and G ‐tests of independence and Kruskal–Wallis tests were used to evaluate relationships among individual species distributions, past land‐use, surficial landforms and edaphic conditions. Results At the scale of this investigation, modern species distributions result from individualistic response to a range of environmental and historical factors, including geography, substrate and disturbance history, especially the pattern of past agricultural activity. The structure or composition of all vegetation types in the region have been shaped by past land‐use, fire, or other disturbances, and vegetation patterns will continue to change through time. Conservation efforts aimed at maintaining early successional vegetation types may require intensive management comparable in intensity to the historical disturbances that allowed for their widespread development.

Three hundred years of forest and land‐use change in Massachusetts, USA - Brian Hall; Glenn Motzkin; David R. Foster; Mindy Syfert; John Burk (Journal of Biogeography, 2002)
Aim The aim of this study was to document changes in forest composition, structure and distribution across Massachusetts, USA, from the time of European settlement (seventeenth century) to the present, and to investigate environmental and historical influences on regional patterns of variation. Location The study area encompasses the State of Massachusetts (69.9–73.5°E, 41.3–42.9°N), a 21,000‐km 2 area in the north‐eastern United States. Methods A wide range of historical sources was used to document changes in land use and land cover for the historical period. Witness trees from early land surveys enabled us to evaluate vegetation patterns prior to widespread European settlement, and to compare historical and modern species composition. Nineteenth century maps of forest cover and contemporary agricultural censuses documented forest patterns during the peak agricultural period. Geographic Information System analyses were used to relate variation in climate, geology and land‐use history to historical and modern forest composition. Results Massachusetts has a complex east‐to‐west environmental gradient involving changes in physiography, climate, geology and natural disturbance. Until the middle of the twentieth century, agriculture was the most important land‐use across the region; although the percentage of land in agriculture and the timing of major land‐use changes were remarkably consistent across the state, historical forest patch sizes varied locally and regionally in relation to physiography. Forest composition of both early historical and modern forests is most strongly related to environmental conditions, especially variation in climate. Historical land‐use resulted in a state‐wide increase in early successional tree species and a dramatic, although recovering, change in forest structure. Main conclusions At a regional scale, environmental conditions apparently control broad patterns of variation in vegetation composition. Historical land‐use practices were relatively homogenous across Massachusetts and local variation was reduced through data averaging at broad spatial scales. At finer spatial scales, historical land‐use has strong and persistent impacts on vegetation composition and structure.

Oak, chestnut and fire: climatic and cultural controls of long‐term forest dynamics in New England, USA - David R. Foster; Susan Clayden; David A. Orwig; Brian Hall; Sylvia Barry (Journal of Biogeography, 2002)
Aim Despite decades of study we have limited insights into the nature of the pre‐European landscape of the north‐eastern USA and the forces and changes that shaped modern forest patterns. Information on such long‐term forest dynamics would provide critical insights into the relationships among environmental change, land‐use history and biotic responses and is greatly needed for conservation planning. To address these issues we used modern, historical, and palaeoecological approaches to reconstruct the 3500‐year history of a New England upland region dominated by oak and (formerly) chestnut forests and to interpret the interactions among climate change, natural and human disturbance, and site factors in controlling vegetation patterns and dynamics at different spatial scales. Location The study focused on a broad upland ridge dominated by oak forests in the north‐central Massachusetts town of New Salem. Detailed palaeoecological analyses were undertaken of wetland (Chamberlain Swamp) and lake (Lily Pond) basins in order to reconstruct local to regional scale vegetation dynamics, which were interpreted within the context of regional vegetation data from central Massachusetts. Methods Palaeoecological methods were used to reconstruct the vegetation, fire and land‐use history of the local and subregional vegetation from the two basins and to place these in the context of regional information on vegetation and climate change based on other published data. Historical information including maps, archaeological and census data, and vegetation information were gathered for the landscape and areas surrounding the coring sites. Vegetation sampling in transects adjacent to the swamp coring area included tree cores for dendrochronological reconstructions. Results Stand, landscape and regional forest dynamics were most strongly driven by climate, notably an apparent cooling and increase in moisture availability c. 1500 yr bp , and European land‐use activities commencing 260 yr bp . However, the abundance of oak and chestnut (fire‐tolerant, sprouting species) and the distribution of hemlock (fire‐intolerant) at a stand to landscape scale were also influenced by fire, which, in turn, varied with climate and human activity. Despite, or perhaps as a consequence of ongoing disturbance by fire and presumably windstorms in this hurricane‐prone region, the pre‐European period was marked by two 1000+ year periods of remarkably stable forest composition, separated by an abrupt compositional shift. In contrast, over the past 260 years the vegetation has changed rather continuously in response to human activity, producing stand, landscape and regional patterns that are novel as well as recent in origin. The results indicate that chestnut was a major component of some pre‐European landscapes in New England, in part because of occasional fire, and that cultural and physical factors have interacted over millennia to control vegetation patterns and dynamics. Our analyses also suggest that the composition of low diversity forests can be remarkably stable over millennia. The range of ecological, cultural and management insights afforded by this study underscores the fundamental utility of very long‐term research in science and policy development.

Cultural, environmental and historical controls of vegetation patterns and the modern conservation setting on the island of Martha's Vineyard, USA - David R. Foster; Brian Hall; Sylvia Barry; Susan Clayden; Tim Parshall (Journal of Biogeography, 2002)
Aim Long‐term studies of landscape dynamics in relationship to changes in cultural, environmental and disturbance factors have great potential for increasing the understanding of modern ecological conditions and improving the development of conservation plans that incorporate historically important processes. In this study we compiled archaeological, historical, palaeoecological and ecological information on Martha's Vineyard to investigate temporal and spatial variation in landscape pattern and process. Although 2 , this island off the Massachusetts coast embraces remarkable geographical variation and harbours uncommon plant and animal assemblages that make it a national priority for conservation. Location The study embraces the entire island of Martha's Vineyard, which lies c. 8 km south of Cape Cod and the mainland of Massachusetts. The triangular‐shaped island contains three major geomorphological regions: moraine forms a series of irregular and subparallel ridges and hills 40 to over 80 m in elevation that terminate at the western end of the island in high cliffs at Gay Head and Squibnocket; sandy glacial outwash overlying moraine spreads down the northeastern end of the island forming a region of low undulating hills and shallow depressions 15–30 m in elevation, and an extensive outwash plain stretches across the central and eastern part of the island and slopes gently from 30‐m elevation in the north to 100 m of Quaternary and coastal plain sediments. Methods Long‐term records of vegetation, fire, natural disturbance and human activity were compiled over the past 2000 years and across the physiographic variation on the island. Palaeoecological interpretations of vegetation, fire, climate and land‐use history are based on a series of eleven stratigraphies from ponds, lakes and wetlands; archaeological data were compiled from recent surveys; historical data were assembled from census and town records, fire records, aerial photographs and cartographic series; and ecological information was derived from forestry and conservation surveys and field sampling of vegetation, soils and site characteristics. Extensive use was made of geographical information systems and multivariate statistical analyses. Results Spatial patterns in vegetation over the past 2000 years have varied strongly with soils and physiography, which are also associated with major differences in fire and land‐use history. Mesic hardwood forests that seldom burned occupy the western moraine, open oak‐pine and hardwood forests occur on the frequently burned and dissected outwash plain along the south coast, and pine‐oak forests cover the central outwash plain, which extends across much of the island and displays among the highest charcoal values in New England. Although a relatively large Native American population may have been an important source of fire ignitions there is no palynological or archaeological evidence that this culture cleared substantial areas or directly altered the extent of forest cover. Shifts in forest composition and fire were associated with regional climate change during the pre‐European period, whereas pronounced changes in forest cover and the development of extensive open‐land areas of grassland, shrubland and heathland were driven by European land use. The contrasting characteristics, land‐use histories and ownerships of different regions of the island yield contrasting conservation priorities and management directions. The mesic morainal forests have changed modestly in composition during the historical period and can effectively support a distinct woodland flora if adequately protected. The large outwash plain is broken by non‐native plantations but could yield an effective landscape mosaic of oak and pine forests interrupted by extensive scrub oak barrens that could be maintained through prescribed fire or cutting. In contrast, the south shore grasslands and shrublands are the product of intensive agricultural land use. These habitats and their unusual suite of plants and animals require traditional land‐use practices, or their substitutes, in order to reverse the ongoing increase in woody species and to maintain these cultural landscapes. Main Conclusion The biotic, edaphic, disturbance and historical diversity across this relatively small landscape is remarkable and yet poses many challenges to interpretation and conservation. The modern landscape can only be understood through knowledge of its long‐term past and can be best managed in the context of the natural and cultural factors that have shaped it through time.

Dynamic Modelling of Spatially Variable Catchment Hydrochemistry for Critical Loads Assessment - Helen J. Foster; Matthew J. Lees; Howard S. Wheater; Colin Neal; Brian Reynolds (Water, Air, & Soil Pollution, 2001)

Growth rate and potential climate record from a rhodolith using 14C accelerator mass spectrometry - Brian R. Frantz; Michaele Kashgarian; Kenneth H. Coale; Michael S. Foster (Limnology and Oceanography, 2000)
Rhodoliths, free‐living calcareous red algae, create large and diverse habitats worldwide. Although these plants are abundant and ecologically important, little is known about their growth rate. We determined the growth rate for an individual rhodolith, Lithothamnium crassiusculum , from the southern Gulf of California through 14 C analysis using accelerator mass spectrometry (AMS) to be 0.6 mm yr −1 . This growth rate suggests large L. crassiusculum , which have been found with radii in excess of 6 cm, may live over 100 yr. Declines in the Δ 14 C record associated with the large El Niño events of 1957, 1982, and 1992 indicate 14 C analysis may lead to identification of important climate events in the more distant past. The ability to determine changes in past ocean circulation related to changes in past climatic conditions through AMS 14 C analysis of rhodoliths would increase the geographic range of available climate records from the tropical oceans to the entire global ocean and potentially allow for the determination of past climate conditions from rhodoliths in fossil beds.

A tobacco cryptic constitutive promoter, tCUP, revealed by T-DNA tagging - Elizabeth Foster; Jiro Hattori; Hélène Labbé; Thérèse Ouellet; Pierre R. Fobert; Lisa E. James; V.N. Iyer; Brian L. Miki (Plant Molecular Biology, 1999)